Case Report: Anti-TNF Treatment Failure in a Patient With Immune Checkpoint Inhibitor-Induced Severe Colitis - Leilei Fang; Changqin Liu; Xiaomin Sun; Zhanju Liu (Frontiers in Oncology, 2022)
Immune checkpoint inhibitor (ICI)-induced colitis is one of the known complications of therapies targeting cytotoxic programmed cell death protein 1 (PD-1), cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), and programmed cell death ligand 1 (PD-L1). ICI-associated colitis is routinely treated with immunosuppressive therapy, including corticosteroids and/or agents targeting tumor necrosis factor-α (TNF-α). In this report, a 69-year-old male patient developed severe ICI-induced colitis 2 weeks after anti-PD-L1 mAb (i.e., durvalumab) treatment; unexpectedly failed to respond to systemic corticosteroid, anti-TNF, and anti-integrin agents; and unfortunately died in 1 month. This case reminds clinical physicians to be on the alert for early-onset acute ICI-induced colitis and emphasizes that urgent optimized rescue measures are required for patients with severe ICI-induced colitis.